Kajian Pengendalian Kualitas Lingkungan - Anhar Drakel (Jurnal Ilmiah Wahana Pendidikan, 2022)
Environmental problems arise because of the interaction between economic activity and the existence of natural resources. The greater the amount and intensity of natural resource exploitation, the impact on environmental degradation tends to increase. Impacts or side effects (side effects / externalities) include space and time. In addition, environmental impacts not only have local, regional and global impacts, but also have short, medium and long term impacts on the environment. The problems in this study are as follows: (1) Economic and environmental perspectives in the utilization of natural resources (2) Environmental problems (3) The impact of environmental damage on the economy and society (4) Implications of environmental quality control policies. The objectives of this study are as follows: (1) To find out how the economic and environmental perspectives are in the utilization of natural resources. (2) Examining environmental problems (3) Assessing the impact of environmental damage on the economy and society (4) Knowing and studying the necessary policies in controlling environmental quality. Attention to environmental problems is still not much. Policy formulation and implementation still need to be further developed and perfected. Therefore, it is necessary to support various elements in society so that environmentally sound development efforts can be realized. The role and political will of the government is the main key to its success, in addition to the support and participation of other institutions such as economic actors, especially producers in the industrial and agricultural sectors, non-governmental organizations, the mass media, which together with the support and participation of the community.